Are emergency department junior doctors becoming less experienced in performing common practical procedures?. Issue 9 (21st August 2007) - Croft, Susan J; Mason, Suzanne
Abstract : A questionnaire was designed to measure junior doctors' experience of performing practical procedures and was distributed to all junior doctors working in our emergency department during June 2005 and June 2006. The junior doctors were subjectively less experienced in all the procedures measured in 2006 compared to 2005. There were statistically significant reductions in experience of shoulder manipulation, suturing and wound exploration. Junior doctors are becoming less experienced in performing some practical procedures.